(7x+9=-75)

Simple and best practice solution for (7x+9=-75) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7x+9=-75) equation:



(7x+9=-75)
We move all terms to the left:
(7x+9-(-75))=0
We calculate terms in parentheses: +(7x+9-(-75)), so:
7x+9-(-75)
We add all the numbers together, and all the variables
7x+84
Back to the equation:
+(7x+84)
We get rid of parentheses
7x+84=0
We move all terms containing x to the left, all other terms to the right
7x=-84
x=-84/7
x=-12

See similar equations:

| (7x+8=-75) | | 2t(t–8)=0 | | 0.02x=-1.2 | | 3(4x-8)7+21=9x | | (8x+1=49) | | 22-3w=5w+38 | | 20x-6=90 | | 3x-6+7x+16=180 | | (4x=-29) | | x+10x+25=169 | | 45-c=32 | | 3(x+12x)=-4 | | 440*440h(1/3)=18069333.33333 | | 2x+2(2+x)=-16 | | 13x+16=8x+26 | | x+4x-14=0 | | -6=-36+6m | | 2/3+7m/5=31/15 | | 5/2y-7=23 | | 7x-113x=4 | | Sx4+114=120 | | 9x+3=13x–9 | | 2x+8=12/44 | | y-0.8y=960 | | x²-4x=4 | | 3m2-6m=24 | | 8x+3=27+2 | | D(q)=−29q+625 | | (2x+6)(x-13)=0 | | 714=x+5x/100 | | -7+m=6(3m-4) | | x=7x-3(x+6)=-2 |

Equations solver categories